PENGARUH MODEL PAIKEM GEMBROT TERHADAP PEMBELAJARAN KOOPERATIF TYPE JIGSAW PADA PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - Chrisnaji Banindra Yudha; Evayenny Evayenny; Dyah Anungrat Herzamzam (Prima Magistra: Jurnal Ilmiah Kependidikan, 2021)
This study aims to prove the effect of the  PAIKEM GEMBROT  model on mathematics learning outcomes in fractions material, between students who are given learning with the  PAIKEM GEMBROT  model compared to students taught with the Jigsaw cooperative learning model. This research was conducted for two months to be precise, namely January to March 2019, with a total sample of 60 students, to be precise 30 VD class students who were given using the  PAIKEM GEMBROT  model and 30 students in VA class using the Jigsaw cooperative learning model. . Based on the calculation, it was found that the average learning outcomes of students through the  PAIKEM GEMBROT  model had an average of 73.5. Furthermore, the learning outcomes using the average model are 60.1. Based on the hypothesis test, the value of tcount = 5.101> t table = 2.00172 is obtained. So it can be concluded that H1 is accepted and Ho is rejected. The conclusion of this study is that there is a significant difference between the mathematics learning outcomes of students who are taught using the  PAIKEM GEMBROT  model and the Mathematics learning outcomes using the Jigsaw cooperative learning model on fraction material in class V Jatirangga 03 Bekasi elementary school.